Metaphor and material culture - Tilley, Christopher Y. (Oxford, UK ; Malden, Mass)
xv, 298 sayfa
Keywords: “This book provides an innovative contribution to debates about the use of metaphor in the social sciences written by one of today's foremost archaeological theorists. Christopher Tilley combines theoretical interpretation with practical examples to show the significance of the concept of metaphor in the study and writing of material forms.” --